2022
DOI: 10.3389/fmicb.2022.874908
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Multifunctional GH20 β-N-Acetylglucosaminidase From Chitinibacter sp. GC72 and Its Application in Converting Chitin Into N-Acetyl Glucosamine

Abstract: In this study, a gene encoding β-N-acetylglucosaminidase, designated NAGaseA, was cloned from Chitinibacter sp. GC72 and subsequently functional expressed in Escherichia coli BL21 (DE3). NAGaseA contains a glycoside hydrolase family 20 catalytic domain that shows low identity with the corresponding domain of the well-characterized NAGases. The recombinant NAGaseA had a molecular mass of 92 kDa. Biochemical characterization of the purified NAGaseA revealed that the optimal reaction condition was at 40°C and pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The closer the results are to the real learning experience of students, the more likely they are to persist, especially after long-term practice [2] .…”
Section: Obe Concept 21 Definition and Characteristics Of Obe Conceptmentioning
confidence: 89%
“…The closer the results are to the real learning experience of students, the more likely they are to persist, especially after long-term practice [2] .…”
Section: Obe Concept 21 Definition and Characteristics Of Obe Conceptmentioning
confidence: 89%
“…Moreover, it has been shown that amphibians exposed to Bd exhibit an increased abundance of a bacterial-derived chitin deacetylase [ 22 ], an enzyme that contributes to chitin degradation [ 123 ]. Here we reported the presence of genes linked to chitin degradation in Burkholderiales and Chitinophagales MAGs including glycoside hydrolases from the GH19 [ 124 ], GH20 [ 125, 126 ], and GH23 [ 117, 127, 128 ] families. Noteworthy, GH23 enzymes were mainly identified in Burkholderiales MAGs, while GH20 enzymes were identified only in Chitinophagales MAGs suggesting these taxa may use different/complementary strategies for chitin degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Chitinases have been successfully extracted from various bacterial strains, such as Serratia proteamaculans NJ303, Aeromonas hydrophila NJ303, Chitinolyticbacter meiyuanensis SYBC-H1 and Chitinibacter sp. GC72, for the depolymerization of chitin, 77 , 78 , 79 , 80 highlighting the availability of microbial technology in sustainable NAG production. To improve efficiency, it is necessary to further develop the chitinases separation and purification technologies.…”
Section: Depolymerizationmentioning
confidence: 99%